2022
DOI: 10.1145/3550321
|View full text |Cite
|
Sign up to set email alerts
|

Synapse

Abstract: As smartphones are widely adopted, mobile applications (apps) are emerging to provide critical services such as food delivery and telemedicine. While bring convenience to everyday life, this trend may create barriers for older adults who tend to be less tech-savvy than young people. In-person or screen sharing support is helpful but limited by the help-givers' availability. Video tutorials can be useful but require users to switch contexts between watching the tutorial and performing the corresponding actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…AR offers an innovative approach to alleviate the challenges older adults face with smartphone interaction due to declining fine motor and visual skills. These individuals frequently miss small touch targets, leading to more errors, which has been substantiated by various studies [29,44,56,84]. Though research has suggested usability improvements like adjusted icon sizes [53,60], our participants found that enlarging content often compromised screen layout and reduced available preview information, a sentiment mirrored in earlier studies [103].…”
Section: The Potentials Of Ar For Supporting Older Adults In Independ...supporting
confidence: 76%
See 4 more Smart Citations
“…AR offers an innovative approach to alleviate the challenges older adults face with smartphone interaction due to declining fine motor and visual skills. These individuals frequently miss small touch targets, leading to more errors, which has been substantiated by various studies [29,44,56,84]. Though research has suggested usability improvements like adjusted icon sizes [53,60], our participants found that enlarging content often compromised screen layout and reduced available preview information, a sentiment mirrored in earlier studies [103].…”
Section: The Potentials Of Ar For Supporting Older Adults In Independ...supporting
confidence: 76%
“…Though research has suggested usability improvements like adjusted icon sizes [53,60], our participants found that enlarging content often compromised screen layout and reduced available preview information, a sentiment mirrored in earlier studies [103]. In response, researchers have delved into automatic adjustments to enhance user experience [44,85]. AR, with its capability to project expansive displays, offers a compelling remedy.…”
Section: The Potentials Of Ar For Supporting Older Adults In Independ...mentioning
confidence: 56%
See 3 more Smart Citations